Contributions, potentials and difficulties of the Google Classroom environment for the teaching and learning process (Research, Society and Development, 2021)
Information and communication technologies – ICT are increasingly present in the daily lives of the entire population, interfering in their social, professional and educational relationships. Among the interactive resources provided by ICT are virtual learning environments, cyberspaces that allow the dissemination of content and virtual interaction. Thus, this article presents partial results of a doctoral research, and aims to investigate the contributions, potentials and difficulties of the Google Classroom environment for the teaching and learning process, according to the 4th year students of the course. Integrated Administration in a public school in the city of Paranavaí. The methodology adopted is of a qualitative nature, of the participant observation type, in which a didactic sequence was implemented, using the resources of Google Classroom, associated with the use of simulations. Subsequently, a post-test questionnaire was applied, the results of which are presented in this article. Among the main advantages of the environment listed by students are: facilitate learning; enable a methodological diversification by combining the use of technological resources; the organization and practicality of the environment; and communication and interaction; And as disadvantages: difficulty in accessing the internet and using its resources. It was concluded that the use of the virtual learning environment Google Classroom, can be an excellent tool for didactic-pedagogical purposes, if used in a planned way, as it can facilitate learning, enable a methodological diversification; assist in the organization of content and interaction between participants.Incluir o resumo em inglês.